The formation of perovskite multiple quantum well structures for high performance light-emitting diodes - Yan Sun (Nature Portfolio, 2018)
Perovskite LEDs: annealing nails it Simple thermal annealing up to 100 degree Celsius leads to optimal device efficiency for mixed-cation halide perovskite light-emitting diodes. A team led by Prof Wei Huang from Nanjing Tech University, China demonstrates a simple thermal annealing approach to optimize the constitution of solution-processed mixed organic-cation lead iodide perovskite thin films for light-emitting diodes with external quantum efficiencies up to 8.6%. They find that the optimal constitution can be obtained by annealing at 100 degree Celsius for 10 min when the dominant phase has high luminescence efficiency and homogeneous film morphology. It is fortunate that the optimal constitution of the mixed-cation halide perovskites can be easily obtained by thermal annealing, which opens up the possibility to produce high performance, large area and low cost perovskite light-emitting diodes.